Cabaran integrasi dan kerjasama teknikal dalam pengurusan sumber air di Lembangan Langat, Selangor - Shaharuddin Idrus; Mazlin Mokhtar; Siti Rahil Ismail (Environmental Management Society, Malaysia, 2003)
Water resources management requires an integrated and holistic approach involving many stakeholders if it were support and realise the concept of sustainability. Integrated Water Resources Management (IWRM) is the recommended approach to be practiced in all continents in ensuring a sustainable quantity and good quality of water for various types of uses and users. However, the integrated management is faced with numerous challenges and problems, in realizing the concept of integration itself, and in technical cooperation. This paper attempts to describe and characterize the many issues and aspects pertaining to water resources management in the Langat Basin, Selangor, Malaysia. The drainage basin has and is experiencing a rapid rate of development in various sectors since about three decades ago. This study collates and analysed data obtained from numerous sources. Findings of this study indicate that the issue of water resource management in the basin and the state of Selangor as a whole is facing various challenges and problems pertaining to aspects of integration, technical cooperation, multi stakeholder participation, integration initiatives, integrative analyses and integrated implementation procedures. These challenges need be to be overcome with full commitment by all involved to ensure a sustainable supply of good quality water for the increasing population